Lines of flight - van Lawick, Justine (Murmurations: Journal of Transformative Systemic Practice, 2019)
I am worried about the long-lasting effects of the dominant, neo-liberal and capitalist systems that are having a devastating influence on planet Earth and on the life and relations of all the beings, human and non-human, living in this world. When Gregory Bateson wrote "Steps to an Ecology of Mind" (1974) and "Mind and Nature" (1979), he already made clear that human beings do not see the interconnectedness of everything, and because we do not see it, we break it. The breaking of connections has created fractures, wounds and fragmentations in nature, between people, between humans and non-humans: animals, plants and other matter. This has created a gigantic ecological crisis and a profoundly unethical and unjust world with an ever-growing gap between the rich and the poor, the people with resources and those without. We perform our systemic practice in this context. What is our responsibility? In what way can we resist the destructive powers and support actions of hope: lines of flight (Guattari 2015)? We can find inspiration in other areas where activists formulate manifestos as a start of other hopeful practices. In this paper, I give the example of a group of journalists that started The Correspondent and I invite all readers to think about actions that we could start, maybe with a manifesto for systemic practices? Abstract (Dutch) Ik maak me zorgen over de langdurige effecten van het dominante, neo-liberale en kapitalistische systeem die een vernietigende invloed hebben op de planeet aarde en op het leven en de relaties van alle wezens, menselijk en niet menselijk, die in deze wereld leven. Toen Gregory Bateson "Steps to an Ecology of Mind" (1974) en "Mind and Nature" (1979) schreef, maakte hij al duidelijk dat wij mensen niet zien hoe alles met alles verbonden is en omdat we het niet zien verbreken we de verbindingen. Dat verbreken heeft fracturen, wonden en fragmentatie veroorzaakt in de natuur, tussen personen, tussen mensen en niet mensen: dieren, planten en andere materie. Dit heeft een enorme ecologische crisis veroorzaakt en een wezenlijk onethische en onrechtvaardige wereld met een groeiende kloof tussen de rijken en de armen en mensen met of juist zonder toegang tot middelen. Wij voeren onze systemische praktijken uit in deze context. Wat is onze verantwoordelijkheid? Op welke manier kunnen we ons verzetten tegen de destructieve krachten en acties van hoop: lines of flight (Guattari 2015) ondersteunen? We kunnen inspiratie vinden in andere gebieden waar activisten manifesten formuleren als een begin van andere, hoopvolle praktijken. In dit artikel geef ik het voorbeeld van een groep journalisten die de Correspondent startten en ik nodig alle lezers uit om na te denken over acties die wij kunnen starten, misschien met een manifest voor systemische praktijken?